The Culture of entrepreneurship: a study of the entrepreneurial motivation and attitudes towards business creation in the UAE in comparison to the US and Brazil - Hammad, Khawla Ahmed (2015)
This study demonstrates the cultural dimension and the surrounding environment of different entrepreneurs selected from three countries, the United States of America, the Federative Republic of Brazil, and the United Arab Emirates. The general objective is to understand the difference in the entrepreneurial motives and spirit towards venture creation from the three different countries. After conducting field research and collecting the required data, a deep analysis was conducted to draw a comparison between the three cultures from an individual’s point of view, to help shape a set of proposed recommendations, which could be used to improve the current culture of entrepreneurship in the UAE.